European Forensics Vision and Action Plan 2020: Relation between Science and Practice in their Implementation (Lithuania Example) - JURKA, Raimundas; KUPARKA, Vidmantas Egidijus; MALEWSKI, Hendryk; MATULIENĖ, Snieguolė; BILEVIČIŪTĖ, Eglė (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
Strategic changes in criminology, its expansion to the international level, the role in ensuring security and inter-state relations stemming from creation of the European criminological area evidence of significant and profound changes in the science and practice of criminology; identification and scientific evaluation of the changes is possible through consistent going deep into them as a research object. This is what the authors of the article have begun by winning and implementing the project ‘The concept of implementing European criminology vision 2020 in Lithuania and the main lines of action’ (MIP-089/2014) financed by the Research Council of Lithuania in 2014. The authors of the article developed the scientific concept of implementation of European criminology vision 2020 in Lithuania, analyzed and evaluated institutional efficiency and quality of performance of the criminological investigation system as the main subject of creation of European criminological area, accreditation of the institutions, the condition of criminological didactics, and adherence to the minimum competence requirements for criminology personnel, carried out the managerial, organizational and legal analysis of applying the minimum quality standards in the crime scene as well as working with evidence from the crime scene to the courtroom, identified possible areas of criminology harmonization, and defined the directions and methods of the harmonization. The research allowed submission of the proposals in regard of the European common criminological area creation plan. The authors present the main survey findings and provide insights on the national action plan measures to realize the idea of creation of the common criminological area.